Some Challenges in Designing and Implementing Learning Material for Ubiquitous E-learning Environment: A Descriptive Study - Agarwal, Shalabh; Nath, Asoke (Recent Advances in Mathematical Research and Computer Science Vol. 8, 2022)
Abstract: The present work shows us the different methods used in ubiquitous learning environment and also its merits and demerits. In the present work we have made a systematic study on various issues and challenges in ubiquitous teaching learning methodology. Due to massive development in IT the entire teaching learning process has been changed. The open learning and distance education methodology has drastically changed the teacher student relationship. In open learning system there is no fixed class room concept. The teaching learning process is now transformed towards student centric rather than teacher centric. The new challenge has come i.e. how to prepare learning material appropriate for ubiquitous learning environment. A thorough revision is required for preparing learning material for ubiquitous environment. More research is required and educators from diversified fields must come together to plan and design activity oriented learning resources to made available to technologists for implementation of ubiquitous learning.